2007
DOI: 10.1128/aem.01008-07
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Production of Dihomo-γ-Linolenic Acid in Saccharomyces cerevisiae

Abstract: To make dihomo-␥-linolenic acid (DGLA) (20:3n-6) in Saccharomyces cerevisiae, we introduced Kluyveromyces lactis ⌬12 fatty acid desaturase, rat ⌬6 fatty acid desaturase, and rat elongase genes. Because Fad2p is able to convert the endogenous oleic acid to linoleic acid, this allowed DGLA biosynthesis without the need to supply exogenous fatty acids on the media. Medium composition, cultivation temperature, and incubation time were examined to improve the yield of DGLA. Fatty acid content was increased by chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…Production of DGLA was higher in the cells grown at 15°C than those grown at 20°C, and no DGLA production was observed in the cells grown at 30°C. When the cells were grown in NSD for 7 days at 15°C, the yield of DGLA reached 2.2 mg/mg of dry cell weight (DCW) and the composition of DGLA to total fatty acids was 2.7 % (Yazawa et al 2007a), comparable to the values obtained in the systems of Beaudoin et al (2000) and Domergue et al (2002) as described above. This is the first case for S. cerevisiae of producing C20-PUFA without supplying the exogenous fatty acids.…”
Section: Production Of Long-chain Pufassupporting
confidence: 79%
See 1 more Smart Citation
“…Production of DGLA was higher in the cells grown at 15°C than those grown at 20°C, and no DGLA production was observed in the cells grown at 30°C. When the cells were grown in NSD for 7 days at 15°C, the yield of DGLA reached 2.2 mg/mg of dry cell weight (DCW) and the composition of DGLA to total fatty acids was 2.7 % (Yazawa et al 2007a), comparable to the values obtained in the systems of Beaudoin et al (2000) and Domergue et al (2002) as described above. This is the first case for S. cerevisiae of producing C20-PUFA without supplying the exogenous fatty acids.…”
Section: Production Of Long-chain Pufassupporting
confidence: 79%
“…To construct a complete pathway that allows DGLA biosynthesis without the need to supply exogenous fatty acids in the media, Yazawa et al (2007a) introduced Δ12-desaturase from K. lactis (KlFAD2), rat Δ6-desaturase (rFADS2), and rat elongase (rELO1) genes in S. cerevisiae. DGLA is an encouraging target because it has unique biological activities (Stone et al 1979;Horrobin and Huang 1987;Iversen et al 1991Iversen et al , 1992Rotondo et al 1994;Williams et al 1996;Vassilopoulos et al 1997;Kahler and Du Plooy 1998;Dooper et al 2003;Das 2006), but its natural sources are very limited.…”
Section: Production Of Long-chain Pufasmentioning
confidence: 99%
“…4, for the present strain, the C18:2n-6 peak). Moreover, the better known enzyme introducing a double bond at position 12, delta12 fatty acid desaturase in S. cerevisiae, was implicated as temperature sensitive in our previous work (Yazawa et al 2007(Yazawa et al , 2010.…”
Section: Resultsmentioning
confidence: 89%
“…Our preliminary microscopic observation of S. pombe cells producing ricinoleic acid showed that many cells were arrested with one or two septa (data not shown). , and the Δ12 desaturase activity is temperature dependent (Yazawa et al 2007(Yazawa et al , 2010, we examined whether we could use temperature to regulate CpFah12p activity. In other words, we attempted to overcome the toxicity of CpFAH12 by changing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) PUFA production in transgenic organisms with heterogeneous expression of PUFA producing enzymes has also been extensively studied. [5][6][7] In many cases, Saccharomyces cerevisiae has been used as a favorable transgenic host as the first step because of extensive genetic knowledge of it, but the lipid accumulation in S. cerevisiae is poor. To improve the low lipid content, we have recently established an oleaginous S. cerevisiae, which accumulates lipids in the cell by genetic modifications of the disruption of SNF2, overexpression of DGA1, and expression of LEU2.…”
mentioning
confidence: 99%